A critical perspective on the changing patterns of Lean Six Sigma research. Issue 1 (17th December 2018) - Rodgers, Bryan; Antony, Jiju; Gupta, Sandeep
Abstract : Purpose: The purpose of this paper is to utilise the research patterns of the most prolific contributors to Lean and Six Sigma methodologies over a 15-year period to inform the discussion on whether the methodologies should be or are being integrated. Design/methodology/approach: Structured searches using keywords were carried out using a single database (SCOPUS) to identify the most prolific contributors to research articles in the areas of Lean, Six Sigma and Lean Six Sigma, and thereafter patterns were analysed in five-year periods between 2000 and 2015. Findings: This research demonstrates clear changing and evolving patterns of research activity. Not only is there a clear emergence of research focussed on Lean Six Sigma rather than a single methodology, there are also indications that researchers publish work using different methodologies in response to different challenges. Research limitations/implications: The research is restricted to a single database and includes only the 21 most prolific contributors in each five-year period. The analysis is based on the focus of each peer-reviewed paper contributed to. Practical implications: This research is intended to support and inform organisations which are developing or running business process improvement approaches by demonstrating the flexibility of Lean and Sigma, and evidencing that researchers work across different approaches and combine them when appropriate. Originality/value: This paper provides a unique perspective on the debate for the integration of Lean and Six Sigma by looking at the patterns of work of researchers themselves to identify whether the focus of research has in fact moved on from exclusively lean or Six Sigma to more integrated approaches as has been argued in individual pieces of research.